Comparative efficacy of Doxycycline vs Povidone-iodine for pleurodesis: A Prospective analytical study - Sapkota, Sandeep; Thakur, Binay; Khatiwada, Sagar; Tiwari, Manoj; Bhattarai, Shachee; Kharel, Ashish; Adhikari, Mahesh Mani; Raut, Saujan; Bhattachan, Anup (Nepalese Journal of Cancer, 2026)
Background: Chemical pleurodesis is an effective intervention for managing malignant or recurrent pleural effusions. Both doxycycline and povidoneiodine are widely available, cheaper, but comparative data on pain and efficacy outcomes remain limited.Methodology: A total of 100 patients with symptomatic pleural effusion requiring pleurodesis were included in the study either doxycycline (n=49) or povidoneiodine (n=51) through an intercostal drain. Pain scores were assessed using a visual analog scale (VAS) at preprocedure, 24 hours, and 48 hours postprocedure. Pleurodesis success, time to chesttube removal, complication rates, and followup outcomes were recorded.Results: Baseline characteristics were well balanced between groups. Pain scores at 48 hours were significantly lower in the povidoneiodine group (median 4, IQR 4–5) compared to doxycycline (median 5, IQR 4–6; p=0.006), with a similar trend at 24 hours (p=0.039). Pleurodesis success rates were comparable (doxycycline 89.8% vs. povidoneiodine 84.3%; p=0.415). Median time to chesttube removal was 2 days in both groups (p=0.344). Complication rates and 1 month followup reeffusion outcomes did not differ significantly between groups (all p>0.05).Conclusion: Povidoneiodine pleurodesis achieves comparable efficacy and safety to doxycycline while offering significantly better pain control at 48 hours postprocedure.